Exploring the dream pattern among the nightshift workers: A qualitative study - Suresh, Nisha; Srinivas, Vijayalaya (International Journal of Dream Research, 2020)
Nightshift workers are increasing day by day, but many times, people forget the health and sleep effects caused by the nightshift. One such impact is the altered circadian rhythm, which is very important for proper functioning of the body and a good sleep. This altered circadian rhythm can have an impact on waking and sleep life of the nightshift workers. This qualitative study is to find the dream pattern among the nightshift workers and to find the frequency in dreaming among this group. Dreams are the reflections of the waking life and dream patterns are seen among groups sharing similar wake life experiences. This study is conducted with nine nightshift and nine dayshift workers, dream journal was used to collect the dreams from the participants. The frequency of dreaming is seen more among the nightshift workers. The dream patterns among both the groups are similar but there are dreams that make the nightshift group different from the dayshift. The dreams of the nightshift group includes mainly their friends and the feelings of being stuck/in danger. Also, their dreams were more fantastic in nature and have more emotional content. The study shows that sexual dreams are seen majorly among the nightshift group. This finding can be further used to conduct researches on the impact of nightshift on the sexual health and overall well being of nightshift workers and the reflection of the same in their dreams.